Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Loyalitas Pelanggan - J Jamaluddin; Tengku Liza Tahura Chairunnisa; Bambang Irawan (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
One of the Strategies that the Company can do in order to survive in competition is to increase service quality. Moreover, to get a positive image of its product, the company should increase its image, which would increase sales. This research aimed to test whether service quality and corporate image affect customer loyalty. The type of research used is associative. This research was conducted by distributing questionnaires to 147 customers with a random sampling method. The research used, multiple linear regression analysis, and teohilever. The results showed that partial service quality has a significant influence on customer purchases in PT. Pokhphand, while the price has not had a significant influence on customer loyalty in PT. Pokhphand Jaya Farm. Simultan early, Service quality and company image significantly affect customer loyalty. Therefore the company should aggressively improve the Service Quality and approach my wards’ customers to find out whether the company image will increase customer loyalty in PT. Pokhphand Jaya Farm.